ISO 9000 2000 - An A-Z Guide. - Hoyle, David (Burlington : Elsevier, 2002)
ISO 9000 has undergone a radical revision, changing the focus from requirements born out of situations that experience had shown led to poor product quality to requirements born out of the need for all organizations to continually achieve their objectives and create satisfied customers. The language has changed from procedure to process and the intent is now more aligned to business needs. The concepts, terminology and techniques that pervade the ISO 9000 family of standards are explained. Learn how to apply such concepts as continual improvements, process management, corrective action and sys.
Front Cover; ISO 9000: 2000 An A-Z Guide; Copyright Page; Contents; About the author; Preface; ISO 9000 in a nutshell; A-Z.
Keywords: ISO 9000 Series Standards -- Handbooks, manuals, etc. Quality control -- Standards -- Handbooks, manuals, etc; ISO 9000 Series Standards -- Handbooks, manuals, etc; Quality control -- Standards -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc